Gene discoveries in autism are biased towards comorbidity with intellectual disability. Issue 9 (9th March 2020) - Jensen, Matthew; Smolen, Corrine; Girirajan, Santhosh
Abstract : Background: Autism typically presents with highly heterogeneous features, including frequent comorbidity with intellectual disability (ID). The overlap between these phenotypes has confounded the diagnosis and discovery of genetic factors associated with autism. We analysed pathogenic de novo genetic variants in individuals with autism who had either ID or normal cognitive function to determine whether genes associated with autism also contribute towards ID comorbidity. Methods: We analysed 2290 individuals from the Simons Simplex Collection for de novo likely gene-disruptive (LGD) variants and copy-number variants (CNVs), and determined their relevance towards IQ and Social Responsiveness Scale (SRS) measures. Results: Individuals who carried de novo variants in a set of 173 autism-associated genes showed an average 12.8-point decrease in IQ scores (p=5.49×10 −6 ) and 2.8-point increase in SRS scores (p=0.013) compared with individuals without such variants. Furthermore, individuals with high-functioning autism (IQ >100) had lower frequencies of de novo LGD variants (42 of 397 vs 86 of 562, p=0.021) and CNVs (9 of 397 vs 24 of 562, p=0.065) compared with individuals who manifested both autism and ID (IQ <70). Pathogenic variants disrupting autism-associated genes conferred a 4.85-fold increased risk (p=0.011) for comorbid ID, while de novo variants observed in individuals with high-functioning autism disrupted genes with little functional relevance towards neurodevelopment. Conclusions: Pathogenic de novo variants disrupting autism-associated genes contribute towards autism and ID comorbidity, while other genetic factors are likely to be causal for high-functioning autism.